ANALYSIS OF THE MARKETING MIX STRATEGY (7P) TO INCREASE SALES OF PROCESSED CASSAVA PRODUCTS AT UD "PURNAMA JATI" MEMBER - Abroor, Muhammad Rifqi; Widayanti, Sri; Roidah, Ida Syamsu (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
One of the leading producers and exporters of cassava in the world is Indonesia. Jember Regency is one of the highest cassava production centers in East Java, with an annual production capacity of 9,492 tons. This processed tape food product, typical of Jember Regency, is produced from the high supply of cassava. There is a need to find processed cassava products considering the high interest in tape products because of their unique quality, so this product is much more popular as souvenirs or souvenirs typical of Jember. The research aims to perfect marketing tactics and determine how the marketing mix (7P) influences consumer decisions in purchasing processed cassava products from UD Purnama Jati Jember. Questionnaire methodology is a technique for collecting information through statements or questions asked to respondents. Because the p-value is smaller than 0.05, product, price, place, and employees influence the results of consumer purchasing decisions at UD Purnama Jati. However, because the p-value is more significant than 0.05, we can rule out the possibility that factors related to the product process, physical evidence, or advertising influence consumers' final purchasing decisions